EXPOSURE TO RETAIL CIGARETTES AROUND SCHOOL AND ITS EFFECT ON SMOKING INITIATION STUDENTS IN TEBING TINGGI CITY AND PEMATANG SIANTAR CITY - Abdi Mubarak Syam; Muhammad Zali; Putra Apriadi Siregar; Muhammad Rezebri; Putri Safira; Apriliani Apriliani; Prima Yanti Siregar; Desty Adinda (Journal Analytica Islamica, 2025)
Backgrounds: Indonesia is the second-largest cigarette market in the world, with an increased smoking rate among young people aged 10-18 years. The latest data show that smoking is increasingly common in youth. Tobacco control will reduce public demand for tobacco products, especially if the supply of tobacco can be limited. Methods: This study uses a cross-sectional design; research was conducted in July-November 2022. This study was conducted on 130 junior high and senior high schools with details of 78 schools in Tebing Tinggi City, and Pematang Siantar City has 52 schools. This study will also examine smoking behavior among students as many as 3900 in junior high and senior high school, with the distribution of students in the city of Tebing Tinggi as many as 2340 students, and students in Pematang Siantar as many as 1560 students. This study will take the coordinates of the school and the coordinates of outdoor retailers' cigarettes around the school using GPS and then will be analyzed using QGIS 3.0 to describe the school's coordinates with the coordinates of the cigarette seller. Data analysis of retailers' cigarettes around schools and students' smoking behavior in Tebing Tinggi City and Pematang Siantar City will use the STATA 15. Results: This study's results indicate a relationship between the perception that smoking is cool and the smoking behavior of students in Tebing Tinggi City (P-value=<0.001; OR=7.238). Students who perceive smoking as cool are 7.238 times more likely to smoke. there is a relationship between the perception of smoking as a symbol of friendship and the smoking behavior of students in Tebing Tinggi City (P-value=<0.001= OR=15.206). Students who perceive smoking as a symbol of friendship are at risk 15.206 times greater for smoking. there is a relationship between the perception of smoking as a symbol of friendship/friendship and the smoking behavior of students in Tebing Tinggi City (P-value=<0.001= OR=12.597). Students who perceive smoking as a symbol of friendship/friendship are 12.597 times more likely to smoke. there is a relationship between the perception that smoking is cool and the smoking behavior of students in the last ten days in Tebing Tinggi City (P-value=<0.001= OR=9.798). Students who perceive smoking as cool are 9.798 times more likely to smoke in the previous ten days. there is a relationship between the perception of smoking as a symbol of friendship and students' smoking behavior in the last ten days in Tebing Tinggi City (P-value=<0.001= OR=28.140). Students who perceive smoking as a symbol of friendship are 28.140 times more likely to smoke in the last ten days. And there is a relationship between the perception of smoking as a symbol of friendship/friendship and students' smoking behavior in the previous ten days in Tebing Tinggi City (P-value=<0.001= OR=22.853). Students who perceive smoking as a symbol of friendship/friendship are at risk 22.853 times greater for smoking in the last ten days compared to students who do not have smoking as a symbol of friendship/friendship. There is a relationship between cigarette advertisements around schools and students' smoking behavior in Pematang Siantar City (P-value=<0.001= OR=2.547). Students have never smoked. And there is a relationship between cigarette advertisements around schools and students' smoking behavior in the last ten days in Pematang Siantar City (P-value=<0.001; OR=3.678). Cigarette advertisements around schools have a risk of 3.678 times greater for students smoking in the last ten days. Suggestion: Tebing Tinggi City Government and Pematang Siantar City Government to strengthen SFA bylaws in Tebing Tinggi City and Pematang Siantar City by including a ban on cigarette advertising and sponsorship around schools. The Tebing Tinggi City Education Office and the Pematang Siantar City Education Office are expected to coordinate with the Tebing Tinggi City Civil Service Police Unit Agency and the Pematang Siantar City Civil Service Police Unit Agency to regulate cigarette advertisements around the school area with a radius of 1 Km. Government to make Regional Regulations related to the prohibition of cigarette advertising around schools and cigarette sellers in Tebing Tinggi City and Pematang Siantar City. The Tebing Tinggi City Education Office and the Pematang Siantar City Education Office are expected to coordinate with the Tebing Tinggi City Health Office and the Pematang Siantar City Health Office to provide socialization to students about the dangers of smoking actively.